Nadzwyczajna forma zawarcia małżeństwa według Kodeksu Prawa Kanonicznego z 1917 i 1983 r. - Jakubiak, Tomasz (Ius Matrimoniale, 2014)
Until the Council of Trent for validity of the Marriage no form of its celebration had been required. Although it was not recognized formally in any legal text, the extraordinary form was born with the 1602 Decree. The extraordinary form was comprehensively regulate in decree Ne temere. The legislator in each following code of the canon law published the norm similar to Ne temere decree p. 7-8 which was less restrictive than the previous one. In the analysis of current law of the Latin Church reference to the previous regulations concerning the subject will give a better grasp on the intentions of the legislator (compare CIC 1983, can. 17, 19). The article tries to answer whether there is a possibility to validly contract the marriage by non-catholics in the extraordinary form in circumstances described in canon 1116 although the proprietary law of the community which they belong to doesn’t envisage such possibility. The author in de lege ferenda conclusions sees the necessity to explain whether and when the parties contracting the marriage with two witnesses only are obliged to contact a person competent in assisting to marriage with the use of other available means of communication if they can’t do it in person or public post operator.